A new group of species of Edessa Fabricius, 1803 (Hemiptera: Heteroptera: Pentatomidae) - Fernandes, José Antônio Marin; Campos, Lourival Dias (Zootaxa, 2011)
Three new species of Edessa (E. metallica sp. nov., E. preclara sp. nov., E. splendens sp. nov.) are described which form a distinct species group. The metallica group is characterized by a metallic blue or green dorsal color. Edessa preclara sp. nov. and E. splendens sp. nov. have an Andean distribution, having been collected above 1000 meters in Ecuador and Colombia respectively. Edessa metallica sp. nov. has been collected in Panama. Illustrations of the metasternal process and male and female external genitalia, photographs of the habitus, and descriptions are provided.